A comparison of interactive immersive virtual reality and still nature pictures as distraction-based analgesia in burn wound care. Issue 1 (February 2023) - Patterson, David R.; Drever, Sydney; Soltani, Maryam; Sharar, Sam R.; Wiechman, Shelley; Meyer, Walter J.; Hoffman, Hunter G.
Highlights: Using a custom portable water-friendly immersive VR hardware during burn debridement in adults is feasible. During wound debridement, participants reported significantly less worst pain intensity when distracted with VR than in standard wound care without distraction. Contrary to predictions, interactive VR did not increase presence or reduce pain more effectively than nature stimuli viewed in the same VR goggles. Participants gave significantly higher ratings of positive affect during the computer-generated world condition compared to participants' ratings during the nature pictures condition. Abstract: Purpose: Non-pharmacologic adjuncts to opioid analgesics for burn wound debridement enhance safety and cost effectiveness in care. The current study explored the feasibility of using a custom portable water-friendly immersive VR hardware during burn debridement in adults, and tested whether interactive VR would reduce pain more effectively than nature stimuli viewed in the same VR goggles. Methods: Forty-eight patients with severe burn injuries (44 adults and 4 children) had their burn injuries debrided and dressed in a wet wound care environment on Study Day 1, and 13 also participated in Study Day 2. Intervention: The study used a within-subject design to test two hypotheses (one hypothesis per study day) with the condition order randomized. On Study Day 1, each individual (n = 44 participants) spent 5 min of wound care in an interactive immersive VR environment designed for burn care, and 5 min looking at still nature photos and sounds of nature in the same VR goggles. On Study Day 2 (n = 12 adult participants and one adolescent from Day 1), each participant spent 5 min of burn wound care with no distraction and 5 min of wound care in VR, using a new water-friendly VR system. On both days, during a post-wound care assessment, participants rated and compared the pain they had experienced in each condition. Outcome measures on Study Days 1 and 2: Worst pain during burn wound care was the primary dependent variable. Secondary measures were ratings of time spent thinking about pain during wound care, pain unpleasantness, and positive affect during wound care. Results: On Study Day 1, no significant differences in worst pain ratings during wound care were found between the computer-generated world (Mean = 71.06, SD = 26.86) vs. Nature pictures conditions (Mean = 68.19, SD = 29.26; t < 1, NS). On secondary measures, positive affect (fun) was higher, and realism was lower during computer-generated VR. No significant differences in pain unpleasantness or "presence in VR" between the two conditions were found, however. VR vs. No VR. (Study Day 2): Participants reported significantly less worst pain when distracted with adjunctive computer generated VR than during standard wound care without distraction (Mean = 54.23, SD = 26.13 vs 63.85, SD = 31.50, t(11) = 1.91, p < .05, SD = 17.38). In addition, on Study Day 2, "time spent thinking about pain during wound care" was significantly less during the VR condition, and positive affect was significantly greater during VR, compared to the No VR condition. Conclusion: The current study is innovative in that it is the first to show the feasibility of using a custom portable water-friendly immersive VR hardware during burn debridement in adults. However, contrary to predictions, interactive VR did not reduce pain more effectively than nature stimuli viewed in the same VR goggles.